The "Choices" of the Economic System in Algeria Since ‎Independence - Kada ‎ AKACEM ‎; Kamel BENMOUSSA (Dirassat Journal Economic Issue, 2016)
This paper aims to return to nature, the reasons for the unwise choices of economic systems to adopt since independence. The essential characteristic of these choices is the glaring absence, at each stage, of national debate in the broadest sense: universities, unions, political parties.